Reviews (Modern theology, 2000)
Books reviewed: Stanley Hauerwas Sanctify Them in the Truth: Holiness Exemplified Tyler T. Roberts Contesting Spirit: Nietzsche, Affirmation, Religion Michael Fishbane The Exegetical Imagination: On Jewish Thought and Theology Kevin J. Vanhoozer Is There a Meaning in This Text? Thomas A. Carlson Indiscretion: Finitude and the Naming of God William J. Abraham Canon and Criterion in Christian Theology: From the Fathers to Feminism Mark. A. McIntosh Mystical Theology: The Integrity of Spirituality and Theology Susan K. Wood Spiritual Exegesis and the Church in the Theology of Henri de Lubac Stephen E. Fowl Engaging Scripture: A Model for Theological Interpretation Nicholas Boyle Who Are We Now? Christian Humanism and the Global Market from Hegel to Heaney